2006
DOI: 10.1128/iai.74.1.769-772.2006
|View full text |Cite
|
Sign up to set email alerts
|

A σ 28 -Regulated Nonflagella Gene Contributes to Virulence of Campylobacter jejuni 81-176

Abstract: A Campylobacter jejuni 81-176 mutant in Cj0977 was fully motile but reduced >3 logs compared to the parent in invasion of intestinal epithelial cells in vitro. The mutant was also attenuated in a ferret diarrheal disease model. Expression of Cj0977 protein was dependent on a minimal flagella structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 39 publications
(31 reference statements)
4
63
0
1
Order By: Relevance
“…It is likely that the genes involved in type 1 pili synthesis and other adhesion/invasion factors are controlled at the transcription level by FliA. Although the involvement of FliA in the regulation of virulence determinants other than flagella has been described in several pathogenic bacteria (18,25,26,28), these studies did not identify intermediate steps linking FliA to the regulation of virulence determinants. In our study, we identified the FliA-dependent yhjH gene as such a mediator.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…It is likely that the genes involved in type 1 pili synthesis and other adhesion/invasion factors are controlled at the transcription level by FliA. Although the involvement of FliA in the regulation of virulence determinants other than flagella has been described in several pathogenic bacteria (18,25,26,28), these studies did not identify intermediate steps linking FliA to the regulation of virulence determinants. In our study, we identified the FliA-dependent yhjH gene as such a mediator.…”
Section: Discussionmentioning
confidence: 50%
“…These flagellar regulators have been shown to affect the synthesis of virulence factors, directly and indirectly, such as secreted hemolysin in Proteus mirabilis (19), the type III secretion system-1 in Salmonella (20), the Lap phospholipase in Y. enterocolitica (21)(22)(23), an exoenzyme in Xenorhabdus nematophila (24,25), an invasion factor in C. jejuni (26), and factors involved in the intracellular growth of L. pneumophila in amoebas and determinants for the cytotoxicity against macrophages (27,28). Together, these findings indicate that coordinated regulation of motility and virulence factor synthesis is not limited to Enterobacteriaceae.…”
mentioning
confidence: 99%
“…Deletion of Cj0256 results in decreased motility and an approximately 95% reduction in flagella production, suggesting that modification of FlgG with pEtN may impart structural stability between the FlgG subunits. Similarly, it has been proposed that glycosylation of filament proteins may provide additional stability to the flagellar filament (25,26). Still, it is not possible to rule out that Cj0256 modifies other targets that play a role in flagellar assembly.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike Salmonella spp., which use T3SSs and translocated effector proteins to manipulate host cells for invasion and intracellular survival, C. jejuni lacks genes encoding these virulence factors. Instead, C. jejuni is thought to take advantage of the flagellar T3SS to secrete potential effector proteins that may assist in invasion and intracellular survival processes (217,339,559).…”
Section: Invasion Of Intestinal Epithelium and Intracellular Replicationmentioning
confidence: 99%
“…Also potentially included as class 2 genes are fliA and flgM, which encode 28 and its anti-factor, since some evidence exists that expression of these genes is partially 54 dependent (80,650). Class 3 genes include those dependent on 28 for expression, which include flaA, genes encoding minor filament proteins, and a few nonflagellar genes that may encode proteins involved in virulence mechanisms (217,489). This transcriptional hierarchy accounts for the requirement of two alternative factors for tight and ordered control of flagellar genes for proper biosynthesis of the flagellar organelle.…”
Section: Transcriptional Regulatory Cascades For Flagellar Gene Exprementioning
confidence: 99%